Crowdfunding Strategies for 3D Printing - Arrahima, Irea (P3M Politeknik Negeri Media Kreatif, 2024)
Crowdfunding is an innovative way for startups to raise the funds they need to launch or grow their businesses. And by turning to the crowd for funding, startups can reap a variety of additional benefits beyond the acquisition of funds. The novelty of this research is that it focuses on a 3D Printing project on crowdfunding platform, considering the past data of backers dan funding value which expected to be used for startup business, especially 3D printing projects as a strategy to increase funding investment on crowdfunding platform. This research was conducted to analyze the crowdfunding strategies can be used by the project owner and to stimulate investment backers as a strategy to increase crowdfunding investment.